The Mellon Retrospective Cataloguing Project in Trinity College Library Dublin - MAWE, SHANE (My University, 2010)
This article describes the Mellon Retrospective Cataloguing Project in Trinity College Library Dublin. It gives a description of the Printed Catalogue (holdings up to 1872) and the Accessions Catalogue (1873-1963) and provides an insight into the work of the project over its four year lifetime (2005-2009). The methodology used to co-ordinate the project is outlined as is the sourcing of electronic records for titles contained in both catalogues. It also shows how advances in a dynamic library environment can affect a project during the various stages of its lifecycle. It suggests options for future conversion projects as well as offering advice to institutions undertaking a comparable task.
PUBLISHED
Keywords: Library catalogues; Special collections; Trinity College; Ireland; Library catalogs Automation; Library catalogs and users